Analysis Of Sgot And Sgpt Levels Using A Photometer ( Microlab L300) And Auto Chemistry Analyzer (Glory 917) At Sapta Medika Hospital - Ega Dewani Putri; Fitri Handayani Siregar; Sri Muri Dasa Wardhani (STABN RADEN WIJAYA WONOGIRI, 2020)
The liver is the most complex metabolic organ in the body. Liver function tests indicate the extent of liver damage. This practicum was conducted at the Integrated Laboratory Center of Syarif Hidayatullah State Islamic University, Jakarta, to understand liver function and understand its role. draft activity specific Glutamate Pyruvate Transaminase (GPT) and Glutamate Oxaloacetate Transaminase (GOT). The tools and materials used in this practicum include test tubes, syringes, vaccutainers, centrifuges, Zenix 188, dextran, serum, reagents R1 and R2, and aquabidest. The results obtained were that the six probands had normal SGPT and SGOT levels, while the normal SGPT level in men is 0-41 u/L and in women is 0-31 u/L.